Recent advancements and future requirements in vascularization of cortical organoids - LaMontagne, Erin; Muotri, Alysson R.; Engler, Adam J. (Frontiers in Bioengineering and Biotechnology, 2022)
The fields of tissue engineering and disease modeling have become increasingly cognizant of the need to create complex and mature structures in vitro to adequately mimic the in vivo niche. Specifically for neural applications, human brain cortical organoids (COs) require highly stratified neurons and glial cells to generate synaptic functions, and to date, most efforts achieve only fetal functionality at best. Moreover, COs are usually avascular, inducing the development of necrotic cores, which can limit growth, development, and maturation. Recent efforts have attempted to vascularize cortical and other organoid types. In this review, we will outline the components of a fully vascularized CO as they relate to neocortical development in vivo. These components address challenges in recapitulating neurovascular tissue patterning, biomechanical properties, and functionality with the goal of mirroring the quality of organoid vascularization only achieved with an in vivo host. We will provide a comprehensive summary of the current progress made in each one of these categories, highlighting advances in vascularization technologies and areas still under investigation.